Antioxidant and hepatoprotective activity of Lannea barteri methanol leaf extract - Florence Nwakaego Mbaoji; Akachukwu Marytheresa Onwuka; Ikechukwu Emmanuel Peter; Cynthia Chioma Mbaoji; Kelvin Chibuzo Uzodinma (African Journal of Pharmaceutical Research and Development (AJOPRED), 2024)
Lannea barteri is a dioecious plant that is widespread in North and West Africa. It is used in the folkloric treatment of many disease states ranging from epilepsy, diarrhoea, oedema and ulcer etc. This study investigated the antioxidant and hepatoprotective effects of Lannea barteri methanol leaf extract (LBME). The in vitro models used were α, α- diphenyl-β-picrylhydrazyl (DPPH), reducing power and thiobarbituric acid assay (TBA) while the in vivo model, carbon tetrachloride- (CCl4) induced oxidative hepatic damage in rat was used. The biomarkers assayed in the in vivo study were aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), malondialdehyde (MDA), serum total protein, and serum total bilirubin. In the reducing power assay, LBME gave the highest activity (35.04%) than Silymarin (26.88%) at 400 µg/ml.  In the DPPH free radical scavenging test, Silymarin gave the highest percentage inhibition (97.37%) than the LBME (91.3%) at 400 µg/ml. In the TBA assay, the LBME gave a higher percentage inhibition (31.15%) than Silymarin (24.8 %) at 400 µg/ml. In the in vivo assay method, the LBME gave some level of protection to the liver by preserving its enzyme more than Silymarin although not significant. Total serum proteins were preserved while total bilirubin and MDA were reduced when compared to the CCl4 group. LBME- (100 mg/kg) treated group significantly (p < 0.05) decreased ALP when compared to the CCl4 treated-group. The phytochemical analyses revealed the presence of alkaloids, carbohydrates, fats and oils, flavonoids, glycosides, proteins, tannins, terpenoids, steroids, and resins. Mice receiving LBME (10–5000 mg/kg) orally did not perish nor develop any sign of acute intoxication, indicating that the extract is extremely safe. This study demonstrated that L. barteri leaf extract has antioxidant activity and protected the rat liver against damage caused by carbon tetrachloride.